GAMBARAN KONSUMSI GARAM BERDASARKAN PEDOMAN GIZI SEIMBANG PADA IBU RUMAH TANGGA - suriani rauf; Rabiatul Adwiah (Jurusan Gizi Poltekkes Kemenkes Makassar, 2017)
Background: Excessive salt intake could increase the risk of high blood pressure or hypertension. The recommended dose limits Balanced Nutrition Guidelines (PGS) in 2014 ie 5 g / person / day equivalent to 1 tea spoon.Aims: This study aimed to describe the consumption of salt based on a balanced nutrition guidelines Housewife in Kassi Kebo District of Maros Baru.Method: This research was a descriptive cross sectional study. Samples were housewives who were in the neighborhood Kassi Kebo Village, Baju Bodoa District of Maros Baru numbering 97 people selected by purposive sampling. Salt consumption was obtained by the method of 2 x 24 hour recall questionnaire.Result: The results showed that salt consumption in housewives were generally classified as either 78.6% and the average amount of salt consumed 4.1 grams / day less than the standard PGS was 5 salt / daySuggestion: It was recommended that those housewives in Kassi kebo to keep the amount of salt consumed.Key words : Salt Consumption, PGS 2014